1990
DOI: 10.1161/01.atv.10.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Different efflux pathways for high and low density lipoproteins from porcine aortic intima.

Abstract: To study the efflux of high (HDL) and low (LDL) density lipoproteins from the arterial wall In vivo, a surgical model in pigs was used. An isolated segment of the lesion-free thoracic aorta was pulse labeled from the lumen of the artery with 3 H-cholesteryl ester labeled HDL and 14 C-cholesteryl ester labeled LDL. Subsequently, the labeled aortic segment was exposed to cold chase In vivo. The transfer of HDL cholesteryl ester from plasma Into intima expressed as intlmal clearance was three to seven times great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…A similar relation between particle size and intimal clearance of HDL and LDL has been demonstrated in humans 29 and pigs. 30 In the previous studies cited, labeled free and esterified cholesterol was employed; our investigation, employing iodinated lipoproteins, has confirmed that such an inverse relation exists and excludes the notion that the previous demonstrations were influenced by the mathematical methods employed. 38 The relation is true even for LDL, IDL, and VLDL, for which the differences in average diameter are only about 30%; in the earlier studies cited, the differences in diameter between the lipoprotein fractions examined were twofold to threefold.…”
Section: Lipoprotein Size As a Determinant Of Arterial Influxsupporting
confidence: 62%
See 1 more Smart Citation
“…A similar relation between particle size and intimal clearance of HDL and LDL has been demonstrated in humans 29 and pigs. 30 In the previous studies cited, labeled free and esterified cholesterol was employed; our investigation, employing iodinated lipoproteins, has confirmed that such an inverse relation exists and excludes the notion that the previous demonstrations were influenced by the mathematical methods employed. 38 The relation is true even for LDL, IDL, and VLDL, for which the differences in average diameter are only about 30%; in the earlier studies cited, the differences in diameter between the lipoprotein fractions examined were twofold to threefold.…”
Section: Lipoprotein Size As a Determinant Of Arterial Influxsupporting
confidence: 62%
“…In keeping with this, arterial influx of LDL in normal rabbits does not depend on endothelial LDL receptors, 28 and in cholesterol-fed rabbits, 2021 humans, 29 and pigs, 30 arterial influx of lipoproteins depends on lipoprotein particle size. However, from our data it cannot be ruled out that saturation kinetics for arterial influx of lipoproteins might occur at plasma concentrations of LDL, IDL, and VLDL above those examined in the present study.…”
Section: Plasma Concentration Of Lipoproteins As a Determinant Of Artsupporting
confidence: 55%
“…[86][87][88][89][90][91] LDL can also leave the intima again, 88,[92][93][94] but only through the lumen against the pressure gradient generated from blood pressure, whereas LDL particles are too large to penetrate the elastic laminas of the media. 94,95 In other words, LDL gets trapped in the arterial intima and attachment to proteoglycans, or other components of the arterial intima may further facilitate LDL trapping within the intima.…”
Section: Biologymentioning
confidence: 99%
“…Experimental surgical interventions in the pig do not require full aortic transplant. Remarkably, delivery of labeled cholesterol esters, either in the form of LDL or HDL, to a ligated and temporarily bypassed segment of the pig thoracic aorta revealed that HDL passes through the media and enters adventitia efficiently, leading investigators in the late 1980s to conclude that HDL was likely cleared through adventitial lymphatics (70,71). Labeled LDL, by contrast, penetrated only into the intimal layer, indicating specificity in trafficking through the medial wall for labeled HDL.…”
Section: Atherosclerosis and Cholesterol Transport Through Interstitimentioning
confidence: 99%